INCENTIVE SUGGESTIONS OF THE RUSSIAN LANGUAGE AS A MEANS OF DEVELOPING THE SPEECH OF STUDENTS OF THE NATIONAL SCHOOL (E Conference Zone, 2022)
This article deals with the study of the motivational sentences of the Russian language in the national school. From a methodological point of view, for the successful study of a foreign language, it is necessary for students to use knowledge of their native language. The learning situations of the Russian language and literary reading lessons are full of incentive sentences, which are mainly used to organize the lesson and study the subject.